Structural injustice and the legitimacy of the state-centric system. Issue 4 (6th June 2020) - Wolf, Reinhard
ABSTRACT: Catherine Lu's seminal Justice and Reconciliation in World Politics is right to stress the enduring nature of some colonialist structural indignities. It is less clear, however, if structural injustices justify Lu's demand for revolutionary changes of the global order. Before transforming the pluralist state-centric system, we need transparent criteria that help us agree on the severity of structural injustices. Considering Lu's strong focus on the colonialist origins of contemporary injustices, one would also like to know if and how their historical background affects their present moral status. The essay concludes that, in a multicultural global society with diverse moral values, we should focus on tackling the most glaring injustices and on rectifying those where accountabilities are least controversial.